How to Deal with Azerbaijan's Oil Boom? Policy Strategies in a Resource-Rich Transition Economy - Rosenberg, Christoph B. (International Monetary Fund, 1998)
The petroleum-rich former Soviet republics around the Caspian Sea face the dual challenge of managing the transition to a market economy and a booming resource sector. This paper examines this challenge with particular reference to Azerbaijan. The standard "Dutch disease" model is modified to capture the special conditions of transition economies, with specific attention to the pattern of real exchange rate movement. "Transition factors" are found to add to the speed of real appreciation. Non-oil sectors may suffer, but less through the real appreciation than through transition-specific structural problems. The paper describes a medium-term policy strategy for Azerbaijan, relating its prospects to the experience in the 1970s of Ecuador, Indonesia, and Nigeria. The adverse effects of the Dutch disease may be avoided if Azerbaijan pursues policies to promote savings and open trade, and strengthens the supply side through structural policies